Epigenetic regulation and epigenomic landscape in rice. Issue 3 (14th October 2016) - Deng, Xian; Song, Xianwei; Wei, Liya; Liu, Chunyan; Cao, Xiaofeng
Abstract: Epigenetic regulation has been implicated in the control of complex agronomic traits in rice ( Oryza sativa ), a staple food crop and model monocot plant. Recent advances in high-throughput sequencing and the moderately complex genome of rice have made it possible to study epigenetic regulation in rice on a genome-wide scale. This review discusses recent advances in our understanding of epigenetic regulation in rice, with an emphasis on the roles of key epigenetic regulators, the epigenomic landscape, epigenetic variation, transposon repression, and plant development.